DAMPAK PEMBANGUNAN PINTU TOL JATIKARYA TERHADAP KINERJA SIMPANG 4 KRANGGAN: The Impact Of The Development Of Jatikarya Toll Doors On Performance Intersection Of 4 Kranggan - Doni Haidar Nur; AR Indra Tjahjani (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Kranggan intersection in Cibubur City is an intersection with four arms equipped with traffic light signals. Kranggan intersection is the confluence of four roads, namely Jl. Kranggan, Jl. Raya Kalimanggis Jl. Transyogi Barat, and Jl. Transyogi East. This intersection has a condition where long queues often occur at this intersection. especially after the existence of the Jatikarya toll gate, the behavior of the Kranggan 4 intersection has changed the direction of traffic flow, of course, so it is necessary to study how many changes have occurred. The research method used is a quantitative method by collecting road geometric data, intersection geometry and current traffic data in 2021 through direct surveys at the research location as well as traffic data on the Alternative Cibubur (Transyogi) road.Before the existence of the Jatikarya toll gate, it was known that the degrees of saturation for the north and west approaches were 0.80, 1.04 (ds > 0.75 ; saturated), while the south and east approaches produced a degree of saturation (ds) of 0.16 respectively. , 0.30 (ds < 0.75 ; unsaturated). The highest queue length is 387.82 m, the average delay of the resulting intersection is 51.47 sec/pcu and the level of service (LOS) is entered with level E (40-60 sec/pcu). After the presence of the Jatikarya toll gate, it is known that the degree of saturation for the South approach is 0.81 (ds > 0.75 ; saturated), while the North, East and West approaches produce degrees of saturation (ds) of 0.56, 0.11 respectively. , 0.38 (ds < 0.75 ; unsaturated). The highest queue length is 167.87 m, the average delay of the resulting intersection is 13, 72 sec/pcu and enter the the level of service (LOS) with level B (5 – 15 sec/pcu). In traffic conditions in the next 10 years, the performance of the intersection will be very bad, it is known that the degrees of saturation for the north and south approaches are 0.94, 1.37 (ds > 0.75 ; saturated), while the East and West approaches produce degrees of saturation (ds > 0.75 ; saturation). ) respectively 0.19, 0.65 (ds < 0.75 ; unsaturated). The highest queue length is 1353.94 m, the average delay of the resulting intersection is 128.33 sec/pcu and the the level of service (LOS) is entered with the F level (>60 sec/pcu). while the East and West approaches produce degrees of saturation (ds) respectively 0.19, 0.65 (ds < 0.75 ; unsaturated). The highest queue length is 1353.94 m, the average delay of the resulting intersection is 128.33 sec/pcu and the the level of service (LOS) is entered with the F level (>60 sec/pcu). while the East and West approaches produce degrees of saturation (ds) respectively 0.19, 0.65 (ds < 0.75 ; unsaturated). The highest queue length is 1353.94 m, the average delay of the resulting intersection is 128.33 sec/pcu and the the level of service (LOS) is entered with the F level (>60 sec/pcu).